The effects of transcranial alternating current stimulation on memory performance in healthy adults: A systematic review. (February 2022) - Booth, Samantha J.; Taylor, Jason R.; Brown, Laura J.E.; Pobric, Gorana
Abstract: The recent introduction of Transcranial Alternating Current stimulation (tACS) in research on memory modulation has yielded some exciting findings. Whilst evidence suggests small but significant modulatory effects of tACS on perception and cognition, it is unclear how effective tACS is at modulating memory, and the neural oscillations underlying memory. The aim of this systematic review was to determine the efficacy with which tACS, compared to sham stimulation, can modify working memory (WM) and long-term memory (LTM) performance in healthy adults. We examined how these effects may be moderated by specific tACS parameters and study/participant characteristics. Our secondary goal was to investigate the neural correlates of tACS′ effects on memory performance in healthy adults. A systematic search of eight databases yielded 11, 413 records, resulting in 34 papers that included 104 eligible studies. The results were synthesised by memory type (WM/LTM) and according to the specific parameters of frequency band, stimulation montage, individual variability, cognitive demand, and phase. A second synthesis examined the correspondence between tACS' effects on memory performance and the oscillatory features of electroencephalography (EEG) and magnetencephalography (MEG) recordings in a subset of 26 studies. The results showed a small-to-medium effect of tACS on WM and LTM performance overall. There was strong evidence to suggest that posterior theta-tACS modulates WM performance, whilst the modulation of LTM is achieved by anterior gamma-tACS. Moreover, there was a correspondence between tACS effects on memory performance and oscillatory outcomes at the stimulation frequency. We discuss limitations in the field and suggest ways to improve our understanding of tACS efficacy to ensure a transition of tACS from an investigative method to a therapeutic tool.